1990
DOI: 10.1002/jez.1402560416
|View full text |Cite
|
Sign up to set email alerts
|

Fish and amphibian models for developmental endocrinology

Abstract: The hormonal control of ontogeny in fish and amphibians is reviewed. Neuroendocrine regulation and actions of metabolic and osmoregulatory hormones (thyroid, interrenal, pituitary, pancreas, and gut) during amphibian and fish metamorphosis and the parr-smolt transformation of juvenile salmon are considered. The developmental significance of hormones in egg yolk is discussed. It is concluded that the transitions between life-history stages provide many unique opportunities for studying basic endocrine phenomena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0
2

Year Published

1994
1994
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 64 publications
3
23
0
2
Order By: Relevance
“…Maternal corticosteriods have been shown to affect growth rate pulses in damselfish prior to hatching (McCormick and Nechaev 2002), but this study and a study in coho salmon (Stratholt et al 1997) did not find differences in hatching time or development rate as a result of maternal corticosteroids. Maternal thyroid hormones in eggs have long been known for their role in growth and metamorphosis in teleosts and other vertebrate animals (Dickhoff et al 1990 and references therein). In rainbow trout, maternal mRNA has been shown to direct the progression of embryonic development until gastrulation when transcription of the embryonic nuclear genome begins (Nagler 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Maternal corticosteriods have been shown to affect growth rate pulses in damselfish prior to hatching (McCormick and Nechaev 2002), but this study and a study in coho salmon (Stratholt et al 1997) did not find differences in hatching time or development rate as a result of maternal corticosteroids. Maternal thyroid hormones in eggs have long been known for their role in growth and metamorphosis in teleosts and other vertebrate animals (Dickhoff et al 1990 and references therein). In rainbow trout, maternal mRNA has been shown to direct the progression of embryonic development until gastrulation when transcription of the embryonic nuclear genome begins (Nagler 2000).…”
Section: Discussionmentioning
confidence: 99%
“…A possible significance of THs in early fish growth and development was implied by the acute responsiveness of very young fish to antithyroid drugs and hormone supplementation treatments (reviewed by Youson, 1988;Brown and Bern, 1989;Dickhoff et al, 1990). The sensitivity of newly hatched fish to THs was reported by Lam and others who found that T 4 treatment accelerated development and larval metamorphosis, and increased survival rates (Lam, 1980;Lam, 1985;Lam and Sharma, 1985).…”
Section: Thyroid Hormone Synergism With Cortisol In Fish Developmentmentioning
confidence: 99%
“…On connaît le rôle majeur des hormones thyroïdiennes dans la métamorphose des amphibiens. Au cours de cette dernière, des pics plasmatiques successifs de thyroxine, de cortisone et de prolactine (PRL) ont été mis en évidence chez Rana catesbeiana (DICKHOFF et al, 1990). Une augmentation, dans l'hypophyse, de la sous-unité a des hormones glycoprotéiques (TANAKA et al, 1991) et des ARN messagers codant pour l'hormone de croissance (TAKAHASHI et al, 1992) a également été démontrée.…”
Section: Les Mécanismes Neuroendocriniensunclassified
“…Il s'agit, comme pour l'argenture, de l'expression d'adaptats anticipateurs qui prépare le poisson, en eau douce, à sa migration marine. Au cours de la transformation du parr en smolt, des pics plasmatiques successifs d'insuline, de prolactine, de T3 et de T4, d'hormone de croissance et de Cortisol ont été mis en évidence (DICKHOFF et al, 1990 ;BOEUF, 1993). Des travaux effectués sur les Salmonidés, au cours de l'accommodation à l'eau de mer, nous renseignent de plus sur certains des effets de ces hormones.…”
Section: Les Mécanismes Neuroendocriniensunclassified